Desain Pengembangan Kurikulum dalam Pendidikan Agama Islam - Yusgiantara, Akbar; Chayati, Salim; Jannah, Ila; Khuriyah, Khuriyah (TSAQOFAH, 2024)
The lack of flexibility and relevance in the development of Islamic Religious Education (PAI) curricula in Indonesia poses significant challenges, particularly in addressing the needs of modern society and the Society 5.0 era. This study aims to identify fundamental principles for designing relevant and effective PAI curricula and to analyze the strengths and weaknesses of subject-centered, learner-centered, and problem-centered approaches. A qualitative method was employed, utilizing literature analysis from various sources, including scientific journals, books, and official documents published in the last five years. Thematic analysis was conducted through data reduction, presentation, and verification techniques. The results indicate that the ideal development of PAI curricula integrates the principles of relevance, flexibility, efficiency, and continuity. Learner-centered approaches enhance creativity and engagement, while problem-centered approaches improve social relevance. Subject-centered design remains essential as a foundational element of knowledge. The integration of these three approaches produces a curriculum model that not only instills religious values but also equips students with critical thinking skills and problem-solving abilities to address contemporary societal challenges. This study contributes to the transformation of PAI curricula to be more adaptive, relevant, and humanistic.